2020
DOI: 10.1002/pon.5454
|View full text |Cite
|
Sign up to set email alerts
|

What are the psychological effects of mesothelioma on patients and their carers? A scoping review

Abstract: Objective: Despite recent advances in research, malignant mesothelioma remains an incurable and devastating disease, typically bringing shock and emotional distress to patients and carers. Little research has addressed the psychological impact on either group. This scoping review examines the current state of evidence on the psychological effects of mesothelioma on patients and carers, and identifies areas for further research. Methods: We searched PubMed, PsychINFO, CINAHL, the Cochrane Library and Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…1 The personal experience of caregivers seems to be rarely considered compared with that of MM patients, 2 and there is a need for research exploring the experiences of this specific population. 3 Clinically, with its high symptom burden, incurability, rarity, and primarily occupational-industrial causation, MM has a unique psychosocial impact. 4 This unique combination is central to understanding the psychological distress related to MM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The personal experience of caregivers seems to be rarely considered compared with that of MM patients, 2 and there is a need for research exploring the experiences of this specific population. 3 Clinically, with its high symptom burden, incurability, rarity, and primarily occupational-industrial causation, MM has a unique psychosocial impact. 4 This unique combination is central to understanding the psychological distress related to MM.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the mental health of the caregivers of malignant mesothelioma (MM) patients are scarce 1 . The personal experience of caregivers seems to be rarely considered compared with that of MM patients, 2 and there is a need for research exploring the experiences of this specific population 3 . Clinically, with its high symptom burden, incurability, rarity, and primarily occupational–industrial causation, MM has a unique psychosocial impact 4 .…”
Section: Introductionmentioning
confidence: 99%
“…As asbestos exposure is usually connected to industrial activity, MM can be characterised as an occupational disease (Noonan, 2017 ), for which responsibility and intentionality can be traced in companies, purposely exposing their workers to harmful pollutants and prioritising their profit instead of people's safety (Guglielmucci et al, 2014 ). MM patients often feel betrayed by their employers, with consequent anger and claims for compensation (Sherborne et al, 2020 ). These behaviours could be seen as an attempt to minimise feelings of guilt over one own's responsibility for negative health outcomes, to find an external scapegoat to blame and to increase the perceived control over a situation entailing feelings of danger and helplessness (Rothschild et al, 2012 ; Guglielmucci, 2016 ).…”
mentioning
confidence: 99%
“…It is associated with a range of life limiting and debilitating symptoms including breathlessness, pain, cough, lethargy, weight loss and sweating. Studies have reported psychological impacts, including depression, anxiety, low mood, as common (Ball et al, 2016;Dooley et al, 2010;Moore et al, 2010;Sherborne et al, 2020). Often patients enter into complex treatment programs resulting in a range of side effects with no guarantee of benefit.…”
Section: Introductionmentioning
confidence: 99%